Artificial Intelligence Attitude Scale for Teachers: Validity and Reliability Study - Alan, Burcu; Kececi, Gonca; Kirbag Zengin, Fikriye (Dergipark Akad, 2025)
The purpose of this study is to develop a valid and reliable measurement tool that can be used to determine teachers' attitudes towards artificial intelligence technology. In order to determine the content validity, the scale items were analysed by field experts. In addition, pre-application was carried out with 20 teachers. After the necessary changes in the pre- application, the scale was applied to 576 teachers for reliability study and construct validity. The KMO value of scale was calculated as .947. According to the Barlett sphericity results, the chi-square value was found to be significant (X2 (630) =9112.901; p<.001). The exploratory factor analysis (EFA) concluded that 36 items were collected in 4 sub-dimensions. The total contribution of the components to the variance is 63.922%. When the fit indices of the model resulting from confirmatory factor analysis (CFA) were examined (X2/df =2.48; RMSEA=0.072; IFI=0.97; NNFI=0.97; CFI=0.97; NFI=0.96 and RFI=0.95), it was concluded that the structure in EFA was confirmed. The Cronbach Alpha reliability coefficient for the overall scale was .962. The scale has sub-dimensions: the use of artificial intelligence in daily life (16 items), the use of artificial intelligence in education (7 items), not adopting artificial intelligence (7 items), and awareness of artificial intelligence (6 items). After the validity and reliability studies, 36 items were obtained, including 27 positive and nine negative items. Statistical analyses show that the scale developed within the scope of this study is a valid and reliable tool for determining teachers' attitudes toward artificial intelligence technology.
Keywords: Artificial intelligence; Attitude towards artificial intelligence; Scale development; Teachers